Formulation, Physical Characterization, and Stability Study of Nanoemulgel Containing Jatropha curcas Leaves Extract - M. Ainun Najib Aly; Edo Pratama; Jauharotus Shobahah; Tristiana Erawati Munandar; Sukardiman (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Jatropha curcas extract has been identified as a promising herbal remedy for various skin disorders. However, its application is limited by its low water solubility and poor skin permeability. Nanotechnology-based strategies provide a way to overcome these limitations. Objective: This study aimed to develop a new drug delivery system for J. curcas extract as a topical treatment for skin conditions. Methods: J. curcas extract was obtained through maceration. The system included a Carbopol 940-based gel and a J. curcas extract (JCE 10% w/w) nanoemulsion (NE) created using a high-energy method with an ultrasonic homogenizer. The appearance, pH, viscosity, spreadability, particle size, polydispersity index, and zeta potential of the nanoemulgel were assessed to verify its physical properties. Results: The optimal formulation produced a dark green nanoemulgel with a distinctive leafy smell and a semi-solid texture. Physical characterization of the JCE-NE-gel included a pH of 6.3, particle size of 142.67 nm, polydispersity index of 0.248, zeta potential of -23.23 mV, viscosity of 87.881 cP, and spreadability of 6.13 cm. Stability testing showed no significant differences after accelerated stability testing and thermal cycling. Conclusion: The study demonstrated that J. curcas extract (JCE-NE-gel) was successfully incorporated into a nanoemulgel formulation (F4), showing excellent physical properties and stability.